VIBRATION TRAINING OF SMALLER FREQUENCE - Mladen Živković; Katarina Herodek (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Vibration training belongs to the category of non-conventional methods of strength and power development in a short period of time. Mechanical vibrations which exert influence on the body can cause changes in gravitational conditions and thus initiate certain biological responses. Vibration stimuli are applied on the terminal point of the kinematic chain and thus can induce oscillations spreading through the muscle. Regardless of the type of the vibration training applied basic idea is to combine willing muscle activations and muscle stretching with the vibration stimulus. Vibration training utilizing Flexi-bar as an oscillating requisite belongs to the group of trainings where work-outs are performed with the additional vibrational stimulation. Vibrational stimulation of the muscle which is achieved on that occasion is induced by small frequences of 4,6 Hz. The purpose of this paper is to give a review of the contemporary reserach studies which investigate the effects of the utilization of the Flexi-bar, possibilities of its use, and determination of the best positions of the exerciser and the requisite so as to enhance the effect of the work-out on the assigned muscle area.